EVALUATION OF MUCOUS MEMBRANE OF THE ORAL CAVITY MICROCIRCULATION IN PATIENTS WITH MAXILLARY DEFECTS AFTER RESECTION SURGERY DUE TO COVID-19 DISEASE - Xabilov Davron Nigman ugli (Web of Journals Publishing, 2025)
The article deals with changes in the microcirculation of the oral mucosa in patients with maxillary defects that have occurred after resection due to complications caused by COVID-19. The relevance of the study is due to the increased number of patients who underwent surgery against the background of complications of coronavirus infection, which requires an assessment of the state of the microcirculatory bed for the development of effective rehabilitation methods. Special attention is paid to the analysis of the effect of complex treatment, including local and general therapeutic approaches, on the state of microcirculation. The results of the study showed a significant improvement in blood flow parameters in patients who received complex treatment, which confirms its effectiveness in the recovery period. The obtained data emphasize the importance of monitoring the microcirculation of the mucous membrane of oral cavity and individual approach to the treatment of patients with maxillary defects, which contributes to improving clinical results and speeding up rehabilitation.
Keywords: COVID-19, removable denture, jaw defect.